2021
DOI: 10.1111/den.14050
|View full text |Cite
|
Sign up to set email alerts
|

Optical diagnosis of colorectal polyps using novel blue light imaging classification among trainee endoscopists

Abstract: Background: Blue light imaging (BLI) has been shown to improve the characterization of colorectal polyps among the endoscopy experts. We aimed to determine if this technology could be taught to endoscopy trainees while maintaining high accuracy and interobserver agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…LCI has shown to improve the ADR compared to white light (58.7% vs. 46.7%; P<0.01) ( 90 ). LCI also improves detection of SSL and diminutive polyps ( 86 , 95 , 96 ). LCI keeps the color of residual as yellow, similar to white light, and therefore enhances the visibility and detection of the polyps ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCI has shown to improve the ADR compared to white light (58.7% vs. 46.7%; P<0.01) ( 90 ). LCI also improves detection of SSL and diminutive polyps ( 86 , 95 , 96 ). LCI keeps the color of residual as yellow, similar to white light, and therefore enhances the visibility and detection of the polyps ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…Koehn et al reported that BLI can be taught to trainee endoscopists with online module and the improvement in accuracy of polyp characterization seemed to correlate with the years in training. Overall diagnostic accuracy improved from 74.7% (before the training) to 85.4% (after the training), P<0.01 ( 86 ).…”
Section: Electronic Enhancing Techniques (Virtual Chromoendoscopy)mentioning
confidence: 95%
“…In recent years, image-enhanced endoscopy techniques, such as blue light imaging (BLI), narrow-band imaging (NBI), and i-Scan have been developed, enabling clear visualization of microvascular architectures and surface structures of colorectal polyps [8][9][10]. Systematic classifications based on NBI findings have been established, such as the NBI International Colorectal Endoscopic Classification and BLI Adenoma Serrated International Classification (BASIC) [11,12]. Despite these advances, optical diagnosis poses challenges to the implementation of "resect and discard" strategies and artificial intelligence (AI) holds promise in revitalizing optical diagnosis savings [13].…”
Section: Introductionmentioning
confidence: 99%
“…This Web‐based learning system was composed of “pre‐test,” “didactic videos explaining BASIC,” “interactive examples,” and “post‐test assessment.” This system was provided by European BASIC investigators. Although the interobserver agreement in adenoma diagnosis was moderate ( k = 0.52), the efficiency of this Web‐based learning program seemed promising for facilitating comprehension of BASIC classification in gastroenterology fellows 6 …”
mentioning
confidence: 99%
“…Although the interobserver agreement in adenoma diagnosis was moderate (k = 0.52), the efficiency of this Web-based learning program seemed promising for facilitating comprehension of BASIC classification in gastroenterology fellows. 6 Allen et al conducted a randomized control study to clarify the optimal method for teaching NICE classification. Twenty medical trainees were randomized into an inclassroom (a single live-teaching session with an NBI expert) group and a self-directed training (educational tool with recorded audio) group.…”
mentioning
confidence: 99%